Impact of supplementing Limosilactobacillus fermentum MN–LF23 on the eradication of Helicobacter pylori with 14–day standard quadruple therapy: a randomized, double–blind, placebo–controlled trial - Yuyang Zhao; Xiaokang Niu; Yong Zhang; Liang Zhao; Liwei Zhang; Jingjing He; Qi Zhang; Yuejian Mao; Fuqing Wang; Xiaohui Zhao; Ran Wang (Nutrition Journal)
Abstract Background The effect of probiotics on Helicobacter pylori (Hp) infection demonstrates considerable heterogeneity. This study aims to elucidate the role of Limosilactobacillus fermentum MN–LF23 (MN–LF23) in Hp–infected populations. Methods A total of 94 adult patients with confirmed Hp infection were enrolled in this study and randomly allocated to the placebo or MN–LF23 group. Patients initially received either placebo or probiotics along with standard quadruple therapy for 2 weeks, followed by continued administration of either placebo or probiotics for an additional 4 weeks. The eradication of Hp, serum levels of inflammatory factors, and alterations in gastrointestinal symptoms were assessed at weeks 0, 2, and 6, while fecal samples were collected for metagenomic sequencing. Results The results showed no significant difference (P = 1) in the eradication rate between the placebo group (85.11%) and the probiotic group (82.98%). Following treatment, the incidence of constipation, dyspepsia, and Gastrointestinal Symptom Rating Scale (GSRS) scores in the probiotic group were markedly lower (P < 0.05) compared to those observed in the placebo group. Throughout the treatment process, there were no significant differences in TNF–α and IL–1β levels between the two groups. Compared to the placebo group, the probiotic group exhibited a significant increase in beneficial bacteria such as Limosilactobacillus fermentum, Lactiplantibacillus plantarum, Bifidobacterium longum, Coprococcus caltus, and Clostridium butyricum. Conclusion MN–LF23 supplementation did not improve the eradication rate of standard quadruple therapy. However, it significantly reduced the overall GSRS score, improved digestive and constipation symptoms, and promoted the proliferation of beneficial bacteria in the intestine.